Aplicabilidade da metodologia de queda de potencial elétrico em testes de fratura monotônica de aços API em meio ácido - Morani, Leandro Martins (2018)
This dissertation studies the applicability of the Electrical Potential Drop methodology on the evaluation and monitoring of crack growth during monotonic fracture tests of API steels immersed in an acid environment. Fracture mechanics testing in aggressive environments represents a challenge because it is necessary to precisely measure relatively small crack growths in presence of plasticity in the uncracked ligament and the specimen submerged in a corrosive environment. The Electrical Potential Drop methodology presents itself as an alternative capable of overcoming this challenge. Nevertheless, previous adjustments and calibration are necessary, especially considering the presence of a corrosive atmosphere. This work proposes and evaluate calibrations and raw data analysis aiming the improvement of this methodology for monotonic fracture tests in acid environments. The applicability of the Electrical Potential Drop methodology for monotonic fracture tests both in air or acid environment after the proposed calibrations and data analysis was demonstrate